2020
DOI: 10.1080/09640568.2020.1820314
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of place-based governance in the management of development dilemmas: long-term learning from Małopolska, Poland

Abstract: In this paper, we reflect on the evolution of place-based governance from a longterm (15 year) study of rural development initiatives undertaken in a region of Poland as part of its accession to the European Union. We decompose the recursive process of institutional learning arising from initiatives for heritage preservation and rural economic development. In our analysis, we elaborate a typology of unavoidable development dilemmas that must be explicitly managed in order to allow place-based governance to eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Concerning businesses in the case study villages in Europe, small local businesses were moderately present [49,51,54,55]. Small-scale, family-run businesses indicate the economic sustainability of local societies [55,56].…”
Section: A Stakeholder Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Concerning businesses in the case study villages in Europe, small local businesses were moderately present [49,51,54,55]. Small-scale, family-run businesses indicate the economic sustainability of local societies [55,56].…”
Section: A Stakeholder Analysismentioning
confidence: 95%
“…In Latvia and Slovenia,, heritage management includes analyses and strategies spontaneously developed by citizens that have been encouraged to help shape heritage communities [49,50]. The case of Wisniowa, Poland, showed that rural heritage preservation and development was merely a process of conflict resolution by reconciling stakeholders [51]. A value-based, people-centered approach was also carefully tested in the Ruritage project.…”
Section: Labeling Planning and Project-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted support schemes are support from local and central governments for concepts promoting traditional local agricultural practices, small industrial facilities (such as watermills), local household products, services promoting local craft, husbandry, or traditional production techniques for produce, including their commercialisation (Feuer et al 2021).…”
Section: Swot/tows Analysis (Conclusion Of Analyses)mentioning
confidence: 99%
“…They should be protected, mainly by preserving their characteristics. With these resources identified, local governments gain new tools to perform their statutory obligations and implement solutions to stimulate the development in these areas, for example 22 . Identification of places where cultural heritage assets are located is vital for sustainable rural development.…”
Section: Introductionmentioning
confidence: 99%